Effect of Dietary Incorporation of Coriander Seed Meal on Production Performance of Japanese quail - Narala, Bala Chenna Reddy; Dhulipalla, Srinivas Kumar; Konka, Raja Kishore; Kallam, Naga Raja Kumari (Indian Journal of Animal Nutrition, 2019)
The present experiment was conducted to evaluate the effect of incorporation of coriander seed meal (CSM) in the diet on performance and carcass characteristics of Japanese quail. One hundred and fifty day old quail chicks were randomly allotted to five dietary treatment groups with 3 replicates of 10 birds for 5 weeks. CSM was ground and is included at 0% (T1; Control), 0.5 (T2), 1.0 (T3), 1.5 (T4) and 2.0 (T5) per cent levels in iso-caloric and iso-nitrogenous broiler quail diets to meet the nutrient requirements as per NRC, 1994. Body weight gain and feed intake were recorded while feed efficiency was calculated. There was a significant increase (P<0.01) in body weight gain, overall feed intake and improved (P<0.01) FCR with incorporation of CSM at 2.0% in the diet compared to the control group. There was no significant difference in the carcass traits with respect to dressing percentage and percent weight of heart, liver, gizzard or giblet. However, incorporation of CSM at 2.0% level had increased the carcass yield, ready to cook yield (P<0.05) and meat to bone ratio (P<0.01) compared to the control group. The feed cost/kg gain decreased (P<0.01) with incorporation of CSM at 2.0% level in diet. Thus, it is concluded that CSM can be safely incorporated at 2% level in quail diets without any adverse effects.